Custom, Architecture and Language: A Preliminary Study of Minangkabau-Negeri Sembilan Cultural Discussion in Contemporary Era (1968-2025): Adat, Seni Bina dan Bahasa: Studi Awal Diskusi Kebudayaan Minangkabau-Negeri Sembilan dalam Era Kontemporer (1968-2025) - Nopriyasman Nopriyasman; Abdul Harits Ritonga (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The reestablished relationship between Minangkabau and Negeri Sembilan since 1968 has given rise to two distinct perspectives in the cultural discussion, that are: Negeri Sembilan as a component of Minangkabau culture, and Negeri Sembilan as a distinctive cultural entity within the Malay world. This study aims to uncover the perceptions formed in the scholarly discourse on the Minangkabau-Negeri Sembilan relationship from a historical perspective and to elucidate the factors contributing to these perceptions. The research was conducted using a semi-systematic review model, employing a historical perspective and methodology. The data collected consist of scholarly books and academic articles that examine the relationship between Minangkabau and Negeri Sembilan. Findings reveal three major thematic topics. In the realm of tradition, Adat Perpatih is compared with Minangkabau Tradition. Regarding architecture, numerous studies have been undertaken to reveal the influences on Negeri Sembilan Traditional Houses, including comparisons with Rumah Gonjong, or the resulting evolution that incorporates local values. In terms of language, the Negeri Sembilan language is regarded either as a dialect of Minangkabau or of Malay, with each position having its own supporting arguments. This article can serve as a foundational step for advancing the history of Minangkabau-Negeri Sembilan relations.